Hand Hygiene Compliance in an Emergency Department: The Effect of Crowding. (10th September 2015) - Muller, Matthew P.; Carter, Eileen; Siddiqui, Naureen; Larson, Elaine; Merchant, Roland
Abstract Objectives Emergency department (ED) crowding results from the need to see high volumes of patients of variable acuity within a limited physical space. ED crowding has been associated with poor patient outcomes and increased mortality. The authors evaluated whether ED crowding is also associated with reduced hand hygiene compliance among health care workers. Methods A trained observer measured hand hygiene compliance using standardized definitions for 22 months in the 40‐bed ED of a 475‐bed academic hospital in Toronto, Ontario, Canada. ED crowding measures, including mean daily patient volumes, time to initial physician assessment, and daily nursing hours, were obtained from hospital administrative and human resource databases. Known predictors of hand hygiene compliance, including the indication for hand hygiene and the health care workers' professions, were also measured. Hand hygiene data, measured during 20‐minute observation sessions, were linked to aggregate daily results for each crowding metric. Crowding metrics and known predictors of hand hygiene compliance were then included in a multivariate model if associated with hand hygiene compliance at a p‐value of <0.20. Results Hand hygiene compliance was 29% (325 of 1, 116 opportunities). Alcohol‐based hand rinse was used 66% of the time. Nurses accounted for 68% of hand hygiene opportunities and physicians for 18%, with the remaining 14% attributed to nonphysician, nonnurse health care workers. The most common indications for hand hygiene were hand hygiene prior to (35%) and hand hygiene following (52%) contact with the patient or his or her environment. In multivariate analysis, time to physician assessment > 1.5 hours was associated with lower compliance (odds ratio [OR] = 0.67, 95% confidence interval [CI] = 0.51 to 0.89). Additionally, compliance was lower for nonnurse, nonphysician health care workers (OR = 0.51, 95% CI = 0.33 to 0.79) and higher for hand hygiene performed after contact with the patients or his/her environment, compared to hand hygiene performed before contact with the patient or his/her environment (OR = 2.0, 95% CI = 1.5 to 2.7). Daily patient volumes and nursing hours were not associated with hand hygiene compliance. Conclusions ED hand hygiene compliance was low. Increased time to physician assessment was associated with reduced compliance, suggesting an association between crowding and compliance. Strategies that minimize ED crowding may improve ED hand hygiene compliance.